1,3-dihydroxy-5-(tridec-4′,7′-dienyl)benzene: A new cytotoxic compound from Lithraea molleoides - López, Paula Gladys (2005)
A dichloromethane extract from the leaves of Lithraea molleoides (Anacardiaceae), an argentine medicinal plant, showed cytotoxicity on human hepatocellular carcinoma cell line. Bioassay guided fractionation of this extract led to the isolation of a new active 5-alkyl resorcinol: 1,3-dihydroxy-5-(tridec-4′,7′-dienyl)benzene. Chemical structure was established based on spectroscopic data (UV, IR, MS, 1H-NMR, 13C-NMR, COSY). This compound presented cytotoxic activity on 3 human tumoral cell lines: hepatocellular carcinoma cell line-Hep G2 (IC 50±SD of 68±2 μM), mucoepidermoid pulmonary carcinoma cell line-H292 (IC50±SD of 63±5 μM) and mammary gland adenocarcinoma cell line -MCF7 (IC50±SD of 147±5).